Eficiência fotoquímica e trocas gasosas: associação com o período vegetativo e produtivo em plantas de duas cultivares de mamoeiro - Souza, Icaro Leite (2019)
The objective of this work was to investigate the differential responses in the photosynthetic performance of plants of two cultivars of papaya (Carica papaya L.) during vegetative and productive development, objectifying to provide subsidies to breeding programs and agribusiness. The evaluated cultivars were UENF / Caliman 01 (Calimosa), and Rb-001-4 Aliança (Aliança). The evaluations were performed monthly and started after ten days of transplanting the seedlings. In the first period of analysis (out / 2017 to jan / 2018) the plants were in vegetative development while in the second period (Feb / 2018 to May / 2018) the evaluated population had more than 50% of the plants with an open flower, that is , were in productive development. Evaluations of chlorophyll index, transient fluorescence of chlorophyll a and gas exchange were carried out. The test JIP results obtained in the first month after transplanting showed that cv. Aliança had a reduction in the efficiency of electron transport in the final stages of the electron transport chain. Indicating much more transplant stress (even if acclimation of seedlings occurred) than water stress and heat. When comparing the means of the evaluations performed during the vegetative and productive development, it was possible to observe differential behaviors among the plants of the cultivars. It was noticed that in cv. Calimosa, during the productive development, there was a significant reduction in the parameters of photochemical efficiency and gas exchanges. In the cv. Aliança, no significant changes were observed. Through these results, it was observed that the evaluated parameters were efficient in the identification of differential behaviors between the plants of the cultivars Calimosa and Aliança, during the vegetative and productive development.